Optimizing Dye Wastewater Purification: Ultrasonic and Flotation With Ozonation Synergy - Valentin Romanovski; Marina Pilipenko; Alexandr Dubina; Vitaly Likhavitski; Sergey Volodko; Dmitry Moskovskikh; Elena Romanovskaia (Engineering Reports)
ABSTRACT The article presents the results of experimental studies of the efficiency of purification of model and real wastewater from dyeing and finishing industries using pneumatic flotation using an ozone‐air mixture instead of air and a combination of ultrasonic treatment and ozonation. The influence of gas mixture consumption, dye concentration, and ozone concentration in the gas mixture on the cleaning efficiency was studied. The purification efficiency was assessed by optical density and COD. By using an ozone‐air mixture instead of air in the flotation process, an efficiency increase of up to 12 times was achieved. It has also been shown that wastewater treatment efficiency increases by up to 12% when combining ozone‐air flotation with ultrasonic treatment at 630 W and operating frequency 22% ± 10% kHz. This effect may be associated, first of all, with the dispersion of bubbles of the ozone‐air mixture, which leads to an increase in their total surface and, accordingly, to the rise in the kinetics of mass transfer—ozone dissolution.